Alternative Chairing; Academic Chair Conference Presentations from the Fringe - David A Line; Stephen Pyle; Jeffery Youngquist (Academic Chairpersons Conference Proceedings, 2020)
Expectations of Department Chairs focus on managerial functions often at the expense of creativity. However, leadership expectations often require creative responses. This workshop explores the benefits of (and resistance to) creative chairing, and invites the audience to help generate and explore new and creative approaches to being an academic chair.
Keywords: Chair; Creative; Unique; Alternative; ACC-History; Revitalize